PERAN KELOMPOK USAHA NELAYAN DALAM MENINGKATKAN PENDAPATAN NELAYAN DI DESA ADOKI DISTRIK YENDIDORI KABUPATEN BIAK NUMFOR - Yoseb Boari; Amsal Ilindamon; Lusye Debora Rumaropen (Universitas Yapis Papua, 2022)
The purpose of this research is to find out 1). efforts made by fishermen in increasing their income 2). the role of government in increasing fishermen's income, and 3). the obstacles faced by fishermen in increasing their income in Adoki Village, Yendidori District, Biak Numfor Regency. The method used in this research is descriptive analysis. The results of the study show that efforts to increase fishermen's income are through fishing community empowerment programs such as procuring fishing gear for fishermen and work accident insurance assistance at sea and on land provided by the Biak Numfor District Fisheries and Capture Service. While efforts to increase income as an additional addition to the profession as a fisherman, are carried out in several ways as follows: gardening, selling at kiosks, selling cakes, selling areca nut, selling vegetables, selling spices and selling diluted gasoline. Furthermore, the government's efforts to increase fishermen's income are; 1). Fish processing training, 2). capital assistance and fishing gear. 3). Socialization 4). Provision of assistance facilities. Meanwhile, the constraints faced by fishermen in increasing their income are 1). weather, 2). have no money, 3). fishermen's fishing gear is still sober and very simple and environmentally friendly. 4). health risks and bad weather, 5). damaged boat, and 6). tidal